La naturaleza dimensional del voto en las elecciones argentinas de 2015 - Sendra, Mariana (El Colegio de México, 2022)
This article analyzes the impact of the Argentine attitudinal structure on political preferences in the 2015 elections. Using data from lapop 2016-2017, we first identify the map of latent dimensions that structure public opinion. We then test the hypotheses on the effect of these dimensions on voting. The results show that attitudes related to issues of social mobilization, expressed in terms of “rebels vs. conformists”, are the most relevant ones for party choice. The dimensionality of political conflict from the perspective of the electorate has scarcely been studied in Latin America, so it is hoped that the results of this research will be comparable with other cases in the region in the future.